Стрүктүрийн зааглалын уртрагийн дагуух гүний бүсийн геологи- стрүктүр, геохимийн шалгуурын тухайд - Ж.Ган-Очир; А.Готовсүрэн (Geological Issues, 2023)
In this presentation we are presenting reality of existing of Submeridianal. cross country (cross continental), long life, deep siting faulting zone. Many geologists and geo scientists who were investigated territory of Mongolia and nearby countries on background of completely different sources are mentioned about elements of sudmeridianal faulting zone. Main publications are Kalenov A.D. (1947), Komarov Yu.B. Beloglovkin A.A. (1981), Panov B.S., Huang Qin Yin (1988), Stepanov P.P., Volkhonin V.S. (1969), Byamba J., Arvisbaatar N. (2012), Tudev Ts., Chagnaadorj D., Bayar G. (1981), Mordvinova (1995), Dugaraa P. (2012), Amantov V.A., Borzakovskij Yu.A. (1968), Tumurtogoo O. (2009, 2014), Eenjin G. (2015), Polyakov G.V., Obolenskii A.A., Kepejinskas K.B., Sotnikov V.I. (1989). Sotnikov V.I., Berzina A.P., Bold D. (1984), Kovalenko V.I., Yarmolyuk V.V. (1990). Different scale (regional, middle scale and detail ore zone) interpretations of the faulting structures and tectonic features of territory of Mongolia, which done by J.Gan-Ochir during last 40 years gave possibility to identify lot of different scale elements of this Submeridianal cross country structure. Summarizing data of Country scale geochemical mapping, which completed under supervising A.Gotovsuren showed that along the Central Submeridianal faulting zone are determined regional geochemical anomalies of elements such as Cu, Mo, Bi, As, Mn Left and right sides of the Central Submeridional faulting zone are characterized by completely different characters of distribution of Sn, W, Ni, Co et al. Same time regional distribution of elements such as Pb, Zn mostly related to overlapped volcanic belts. Distribution of Zr is shown additional information on position of regional faults which separating Mongolian tectonic super blocks.